2019
DOI: 10.1016/j.energy.2018.10.049
|View full text |Cite
|
Sign up to set email alerts
|

Novel solutions for closed-loop reverse electrodialysis: Thermodynamic characterisation and perspective analysis

Abstract: Closed-loop Reverse Electrodialysis is a novel technology to directly convert low-grade heat into electricity. It consists of a reverse electrodialysis (RED) unit where electricity is produced exploiting the salinity gradient between two saltwater solutions, coupled with a regeneration unit where waste-heat is used to treat the solutions exiting from the RED unit and restore their initial composition. One of the most important advantages of closed-loop systems compared to the open systems is the possibility to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…Shahzad et al presented an increased overall efficiency of the hybrid process [15], while Thu et al reported that hybridisation increases the distillate output of an existing MED plant [16]. Another promising application for adsorption desalination as well as other thermal desalination methods is the combination with Reverse Electrodialysis [17] to generate electricity from low-grade heat in a closed-loop system [18,19]. Membrane distillation [20,21], MED [22], and adsorption desalination [23] have been proposed for the application in closed-loop systems.…”
Section: Introductionmentioning
confidence: 99%
“…Shahzad et al presented an increased overall efficiency of the hybrid process [15], while Thu et al reported that hybridisation increases the distillate output of an existing MED plant [16]. Another promising application for adsorption desalination as well as other thermal desalination methods is the combination with Reverse Electrodialysis [17] to generate electricity from low-grade heat in a closed-loop system [18,19]. Membrane distillation [20,21], MED [22], and adsorption desalination [23] have been proposed for the application in closed-loop systems.…”
Section: Introductionmentioning
confidence: 99%
“…Carati et al [14] presented a theoretical analysis on SGP HE, focusing on the effect of different saltwater solutions, namely NaCl, ZnCl2 and sodium hydroxide (NaOH) water solutions, on the performance of a unit constituted of a distiller and an ideal SGP unit. Similarly, Giacalone et al [15] performed a theoretical analysis concerning the influence of different salt-water solutions, namely NaCl, LiCl, potassium chloride (KCl), potassium acetate (KCH3CO2), caesium acetate (CsCH3CO2) and sodium acetate (NaCH3CO2) water solutions, on the performance of SGP HEs consisting of single and multi-stage regeneration units. Micari et al [16] experimentally investigated the performance of a RED unit fed by aqueous solutions of binary salt mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Heat-to-electricity efficiency vs power density of state-of-the-art technologies to harvest low-temperature heat reported in literature. Red points: thermal regenerative electrochemical cycle systems (TREC); [12,14,48] Black points: thermal electrochemical cell devices (TEC); [20,49,50] Blue points: thermo-osmotic energy conversion technologies (TOEC); [51,52] Orange points: pressure-retarded osmosis systems (PRO); [2,23,53] Purple points: reverse electrodialysis devices (RED), [27,40,54,55] Brown points: TRCBs; [36,56] Green stars: TRBs. [41]…”
Section: Conflict Of Interestmentioning
confidence: 99%